Multicomponent Crystal of Trimethoprim and Citric Acid: Solid State Characterization and Dissolution Rate Studies - Umar, Salman; Farnandi, Rido; Salsabila, Hulwa; Zaini, Erizal (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Trimethoprim is a broad spectrum antimicrobial agent with low solubility in water which causes low bioavailability in systemic circulation. AIM: The purpose of this study was to prepare multicomponent crystals of trimethoprim and citric acid to increase the solubility and dissolution rate of trimethoprim. MATERIALS AND METHODS: Multicomponent crystals were prepared by solvent evaporation method. Characterizations of multicomponent crystalline solid phase properties were carried out by powder X-ray diffraction (PXRD) analysis, differential scanning calorimetry (DSC), FT-IR spectroscopy, scanning electron microscopy (SEM). Solubility and dissolution rate tests were carried out in aqueous medium. RESULTS: The PXRD characterization results showed a new X-ray diffraction pattern in the multicomponent crystal phase. DSC analysis showed the formation of a new endothermic peak. This indicates the formation of a multicomponent crystal phase between trimethoprim and citric acid. The results of the SEM analysis indicate the formation of a new crystal habit. Solubility of multi-component crystal phase of trimethoprim increased 7 times compared to intact trimethoprim. The dissolution of trimethoprim and multicomponent crystals in 0.1 N HCl medium at 60 minutes was 56.36% and 95.57% and CO2-free distilled water medium was 43.03% and 88.26%, respectively. CONCLUSIONS: From the results of the study, it can be concluded that the multicomponent phase of trimethoprim crystals with citric acid successfully increase the solubility and dissolution rate of trimethoprim significantly.